E(x)= (2x-3)la puterea a2-a  - (x+1)

Se cere : E( 1 supra 2): E(-1 supra 2)



Răspuns :

E(x) = (2x - 3)²  - (x+1) 
E(x) = 4x² -12x + 9 - x - 9
E(x) =  4x² - 13x + 9

[tex]E( \frac{1}{2})=4*( \frac{1}{2} )^{2}-13* \frac{1}{2}+9= \\ = \frac{4}{4}- \frac{13}{2}+ 9= \\ =\frac{2}{2}- \frac{13}{2}+ \frac{18}{2} = \\ = \frac{2-13+18}{2} = \\ = \frac{7}{2} [/tex]

[tex]E( \frac{-1}{2} )=4*(\frac{-1}{2})^{2}-13*(\frac{-1}{2}) +9= \\ =4*(\frac{1}{4}) + \frac{13}{2}+9= \\ = \frac{4}{4} + \frac{13}{2}+9= \\ =\frac{2}{2} + \frac{13}{2}+ \frac{18}{2} = \\ = \frac{33}{2} [/tex]